Poetry of the Turkish poet Gulay Sormagech (Features of children’s works) - Arikkarakyzy Е. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2019)
The article aims to compare literary works with the poems of the great representative of Turkish children’s literature - Gulay Sorgecesh and the ideas of Kazakh children’s literature, which are in the process of studying and studying in the Kazakh literary criticism. «Thank You Lord» («Sen yarattın Allah’ım»), «Thanksgiving» («Selam olsun»), «Thank You Rabbime» («Şükür ederim Rabbime»), «Celebration of Nauryz holiday» («Kurban bayrami»), «God’s gift to us» («Allah’tan hediye bize») - to worship Allah and to return to faith, to glorify the Creator through faith, to glorify the greatness of humanity, - expresses the poetry of spirituality - a kind of contentment, kindness, and humane expression.